TAX MORALE PADA PARA PEKERJA DIGITAL DI INDONESIA - Kuntaryanto, Oki; Jati, Agung Nugroho; Purwanti, Titik (Widya Dharma Journal of Business - WIJoB, 2023)
This study aims to examine factors influencing tax morale on digital workers in Indonesia. This study uses survey method by spreading questionnaires to digital workers across Indonesia. Convenience sampling is used as sampling method. There are 45 eligible respondents where the data are ready to be processed. Multiple regression is employed to test the data. Test results show that clean government, government effectviness spending, tax fairness, and tax tarrif are proven to be significantly influenced tax morale. Further studies may explore in deeper way by interviewing respondents in order to avoid questionnaire bias. Keywords : tax morale, digital workers, tax